The role of the Companions in reform, their position on the darkness of Lady Fatimah al-Zahra and her family, peace be upon them, as a model - Kamel, Ass. Pro Kholoud Hamid; Oraibi, Dr. Mohamed Hassan (Thi Qar Arts Journal, 2022)
Definitions of the term “companions” abounded and varied between one writer and another and for one reason or another. Some historians and writers stipulated that someone who is called a companion must have accompanied the Messenger for a period of time or fought with the infidels, and some of them said that whoever witnessed the Messenger was a Companion. He was a contemporary of the Messenger (may God bless him and his family and grant them peace) or was born in his days, so he is a companion...etc of opinions.